The effects of nano encapsulated Syzygium Polyanthum leaves extract inclusion in drinking water - Afifah, A.N.; Zuprizal, Zuprizal; Dono, N.D. (2022)
A study with six treatments in a Completely Randomized Design was conducted to evaluate the effects of nano encapsulated Syzygium polyanthum leaves extract (SpLE) inclusion in drinking water on small intestinal digesta pH and macromorphology in broiler chickens. The treatments were: drinking water without any addition (negative control), drinking water with 50 ppm antibiotic Tetracycline addition (positive control), or drinking water with1 SpLE, 3 SpLE, 1 nano-capsulated SpLE (N-SpLE), and 3 N-SpLE additions. Each experimental treatment was repeated four times with eight birds per replicate pen. The basal diet and drinking water were provided from days 8 to days 35. One-way ANOVA was used to calculate the effect of the treatments. The difference data in present study were separated with Duncan's new Multiple Range Test. Result showed no treatment effect was detected on macromorphology of all segments on the small intestine. However, drinking water inclusion with 3 SpLE reduced digesta pH (P<0.05) in the duodenum and jejunum. Inclusion of 3 N-SpLE reduced digesta pH only in the ileum (P<0.05). Reductions of digesta pH in some segments of the small intestinal might shows beneficial effect of drinking water inclusion with Syzygium polyanthum leaves extract on the intestinal health improvement in broiler chickens. © Published under licence by IOP Publishing Ltd.